Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kepuasan Kerja yang Dimediasi Motivasi Kerja pada Atlet Sepak Bola Amputasi Dibawah Naungan PSAI (Perkumpulan Sepak Bola Amputasi Indonesia): (Perkumpulan Sepak Bola Amputasi Indonesia) - Ilham, Siti Shafia Rizmarini; Assa, Adrie Frans; Winoto, Hery (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study is to determine the Effect of Compensation and Work Environment on Job Satisfaction Mediated by Work Motivation in Amputee Football Athletes Under the Auspices of PSAI (Indonesian Amputee Football Association). The population 165 amputee football atheletes. Sampling of  in this study was 75 respondents from the Indonesian Amputee Football Association. In this study, the population was all amputee football athletes. The sample was taken randomly using a simple non-random sampling technique. Data  collection  is  primary  data  source  and  secondary  data  source. Data analysis  using  SmartPLS-SEM  (Partial  Least  Square–Structural  Equation  Modeling)  SmartPLS 4 program which consisted of validity, reliability and inner model tests. Compensation has no effect on job satisfaction through work motivation, P-value of 0.182 greater than 0.05. This means that there is no intervening between compensation and job satisfaction through work motivation. The work environment has an effect on job satisfaction through work motivation, P-value of 0.006 less than 0.05. This means that there is an intervening between the work environment and job satisfaction through work motivation.